Raconter la transition, ou comment l’État renouvelle ses relations avec les collectivités territoriales - Fanny Rodier; Céline Granjou; Gwenola Le Naour (Développement Durable et Territoires)
This article focuses on the construction of public action in the field of ecological transition through a study of the Ecological Transition Contracts. The analysis uses an approach based on policy narratives and describes the succession of three major narratives partially in tension, carried by different actors/stakeholders. These narratives first present a transition for troubled territories, then a transition by model territories and finally a more inclusive transition for all territories. We show that these narratives attest to a process of collective construction of a meaning given to the transition and to public action around the definition of the role of the State towards the territories in terms of territorial solidarity and equity in particular.